2004 IEEE International Conference on Communications (IEEE Cat. No.04CH37577) 2004
DOI: 10.1109/icc.2004.1313068
|View full text |Cite
|
Sign up to set email alerts
|

MIMO Ricean channel capacity

Abstract: Abstract-This paper presents asymptotic bounds and limits for the ergodic channel capacity of MIMO systems under Ricean channel conditions. It is shown that the ergodic capacity per dimension decreases as the K factor increases in value and approaches a value equal to that of the underlying scattering channel when the number of antennas are large. The accuracy of the bounds is verified by simulations. In addition, a variety of results for the MIMO Ricean channel are brought together to give an overview of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…Consequently, as we vary the LOS matrix the output power is not kept constant. These results fail when we adjust the granular component so as to guarantee a fixed output power [13], [14], [15]. In other words, examples can be found where for a fixed input distribution and a fixed LOS matrix the mutual information either increases or decreases with the Rice factor, depending on the particular form of the LOS matrix [16].…”
Section: D)mentioning
confidence: 98%
“…Consequently, as we vary the LOS matrix the output power is not kept constant. These results fail when we adjust the granular component so as to guarantee a fixed output power [13], [14], [15]. In other words, examples can be found where for a fixed input distribution and a fixed LOS matrix the mutual information either increases or decreases with the Rice factor, depending on the particular form of the LOS matrix [16].…”
Section: D)mentioning
confidence: 98%
“…In order to manipulate IND channels, it is convenient to assemble the variances of the entries of in a gain matrix such that (26) where (2) implies that (27) Also useful are the column-and row-wise averages of , which yield the vectors (28) (29) where we have used to denote the th column of a matrix. The th entry of represents the average of the gains between the various transmit antennas and the th receive antenna while the th entry of represents the average of the gains between the th transmit antenna and the various receive antennas.…”
Section: B Ind Channelsmentioning
confidence: 99%
“…Some authors have studied the effect of the LOS component by forming the channel matrix as a combination of a pure i.i.d. scattered part plus a specular part with all unit entries, weighted by the Ricean K factor [10,11]. The study showed that the ergodic MIMO capacity in Ricean channels decreases with the increase in the contribution of the LOS component.…”
Section: Introductionmentioning
confidence: 98%